Risk of early death in extremely overweight young men. Issue 6395 (17th September 1983) - Sonne-Holm, S; Sørensen, T I; Christensen, U
Abstract : The effect of pronounced obesity in youth on later mortality was studied in 1239 men with extreme overweight, defined as a weight/height 2 greater than or equal to 31 kg/m2, in the population of 331 919 men liable for military service in the Copenhagen area during the period 1943-1977. A random sample of 2948 drawn from the remaining study population served as a control group. All men were followed up until November 1980, by which time 33 deaths had occurred among the extremely overweight subjects compared with 89 in the control group. This gave a mortality ratio (observed to expected number of deaths) of 1.14 (95% confidence limit 0.91-1.40) for controls with a significantly greater mortality of 1.73 (95% confidence limit 1.20-2.41) for obese subjects. The relative risk, estimated from the survival time distributions, was fairly constant around 1.6 throughout the 37 years of observation. Taking into account age at and year of entry in a regression analysis did not change the relative mortality risk. The proportion of natural death was significantly higher in the obese group than in the control group until the age of 30 but not thereafter. Pronounced obesity in youth is a health hazard, manifesting itself particularly in a distinct increase in mortality from natural causes in early adulthood.